Voprosy perenosa trenirovannosti metatelej molota vysokoj kvalifikacii s ispol'zovaniem «fenomena passivnoj aktivacii» - Bondarchuk, A. P. (Vestnik sportivnoj nauki; Sports science bulletin, 2021)
The problem of transferring fitness is central not only in athletics throwing, but in general in the theory and methodology of physical education. This is explained by the fact that in all cases when a certain amount of exercises is used in the training process, interrelationships and mutual influences are formed between them. Moreover, these interrelationships and mutual influences can be both positive and negative. The article provides a scientifically based set of training exercises for hammer throwers, based on the effect of positive transfer of skills. The manifestation of the dominant principle in the dynamics of sports results of throwers is shown.